2022
DOI: 10.3390/ma15062046
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Impact of Surgical Masks Consumption in Italy Due to COVID-19 Pandemic

Abstract: The COVID-19 pandemic suddenly changed the lifestyle of billions of people. Face masks became indispensable to protect from the contagion providing a significant environmental impact. The aim of this work is to propose possible solutions to decrease masks’ impact on the environment. For this reason, different masks (surgical and fabric) were considered, and the CO2 emissions associated with the mask materials production were calculated. Carbon Footprint (CF) for each material composing the masks was evaluated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 26 publications
(31 reference statements)
1
12
0
Order By: Relevance
“…In accordance with the hypotheses highlighted in [ 19 ], decontamination methods should not only demonstrate effective pathogen reduction but also preserve the properties of medical masks without harmful chemical effects for the user. In accordance with that, the whole and cut mask samples were analyzed for the presence and content of surfactants before and after the first and fifth wash cycle, depending on the composition of the applied detergents and DDAC.…”
Section: Resultssupporting
confidence: 61%
See 1 more Smart Citation
“…In accordance with the hypotheses highlighted in [ 19 ], decontamination methods should not only demonstrate effective pathogen reduction but also preserve the properties of medical masks without harmful chemical effects for the user. In accordance with that, the whole and cut mask samples were analyzed for the presence and content of surfactants before and after the first and fifth wash cycle, depending on the composition of the applied detergents and DDAC.…”
Section: Resultssupporting
confidence: 61%
“…Research has confirmed that disposable face masks belong not only to personal protective equipment (PPE) that greatly contributes to the protection of people [ 18 , 19 , 20 ] but also to the generation of textile waste [ 21 , 22 ]. The problem of the accumulation of textile waste gave rise to the idea of reusing medical masks after decontaminating them in the process of washing them with detergents at 60 °C and treating them with disinfectants, such as hydrogen peroxide, UV rays, moist heat, dry heat, ozone, ethanol, and sodium hypochlorite [ 7 , 19 , 20 , 23 , 24 ]. Decontamination procedures, along with effective pathogen reduction, should preserve the protective features of medical masks (filtration efficiency and breathability) without the harmful chemical effect on the user [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Still, in this study the effect of laces is negligible. To calculate the overall environmental impact of those facial mask productions, if we consider only the case of Italy as an example, it is necessary to calculate the number of masks needed for each person in the country, and some hypotheses were made by Cornelio et al (2022). Assuming that the masks should be changed every eight hours, for workers it was considered two masks per day, for five days/week and one mask/per day during the weekend.…”
Section: Resultsmentioning
confidence: 99%
“…According to Kumar et al [ 43 ], transporting a 10-ton of PPE waste—including face masks, to a 10 km disposal site could result in a GWP impact of 2.76 kg CO 2 Eq. In addition, improper treatments and disposal of the facemask is also a factor that contributes to GHG emission [ 44 ].…”
Section: Resultsmentioning
confidence: 99%